Classification of Chronic Leukemias, Chronic Myeloid Leukemia, Chronic Lymphocytic Leukemia, Erythremia, Myeloma Disease (American Journal of Pediatric Medicine and Health Sciences (2993-2149), 2025)
Chronic leukemia is a primary tumor disease of the hematopoietic system, the substrate of which is immature and mature cells of the myeloid or lymphoid lineage. Various forms of chronic leukemia occur with a predominance of intoxication (weakness, arthralgia, ossalgia, anorexia, weight loss), thrombohemorrhagic (bleeding, thrombosis of various localization), lymphoproliferative syndromes (enlarged lymph nodes, splenomegaly, etc.). Of decisive importance in the diagnosis of chronic leukemia is the study of a complete blood count, bone marrow biopsy and lymph nodes. Treatment of chronic leukemia is carried out using chemotherapy, radiation therapy, immunotherapy, and bone marrow transplantation is possible.